Fit to Perform: An Investigation of Higher Education Music Students’ Perceptions, Attitudes, and Behaviors toward Health - Araújo, Liliana S.; Wasley, David; Perkins, Rosie; Atkins, Louise; Redding, Emma; Ginsborg, Jane; Williamon, Aaron (Frontiers in Psychology, 2017)
Making music at the highest international standards can be rewarding, but it is also challenging, with research highlighting pernicious ways in which practicing and performing can affect performers’ health and wellbeing. Several studies indicate that music students’ perceptions, attitudes, and behaviors toward health and healthy living are less than optimal, especially considering the multiple physical and psychological demands of their day-to-day work. This article presents the results of a comprehensive screening protocol that investigated lifestyle and health-related attitudes and behaviors among 483 undergraduate and postgraduate students (mean age=21.29 years ±3.64; 59% women) from ten leading conservatoires. The protocol included questionnaires measuring wellbeing, general health, health-promoting behaviors, perfectionism, coping skills, sleep quality, and fatigue. On each measure, the data were compared with existing published data from similar age groups. The results indicate that music students have higher levels of wellbeing and lower fatigue than comparable samples outside of music. However, they also reveal potentially harmful perceptions, attitudes, and behaviors toward health. Specifically, engagement in health responsibility and stress management was low, which along with high perfectionistic strivings, limited use of coping skills, poor sleep quality, and low self-rated health, paints a troubling picture both for the music students and for those who support their training. The findings point to the need for more (and more effective) health education and promotion initiatives within music education; in particular, musicians should be better equipped with mental skills to cope with constant pressure to excel and high stress levels. In part, this calls for musicians themselves to engage in healthier lifestyles, take greater responsibility for their own health, and be aware of and act upon health information in order to achieve and sustain successful practice and performance. For that to happen, however, music educators, administrators, and policy makers must play an active role in providing supportive environments where health and wellbeing is considered integral to expert music training.